Case Report: Functional Outcome of COVID-19 Subjects With Myasthenia Gravis and Critical Illness Polyneuropathy - Intiso, Domenico; Centra, Antonello Marco; Amoruso, Luigi; Gravina, Michele; Rienzo, Filomena Di (Frontiers in Neurology, 2022)
Background The COVID-19 disease can affect subjects suffering from myasthenia gravis (MG) and worsen its clinical course, leading to intensive care unit (ICU) admission. Critically ill subjects can develop a neuromuscular complication called ICU-acquired weakness (ICUAW). This disorder has also been detected in ICU subjects with COVID-19, but the association between MG and ICUAW has never been described in critically ill patients. We describe the case and functional outcome of a COVID-19 patient suffering from MG who developed critical illness polyneuropathy (CIP). Case Presentation A 66-year-old man with a history of hypertension and ocular MG had COVID-19 and required ICU admission. The patient underwent mechanical ventilation and tracheotomy and was treated with remdesivir and corticosteroids. Fifteen days after admission, he complained of tetraparesis without the ocular involvement that remained unchanged despite the increase in anticholinesterase therapy. The length of stay (LOS) in ICU was 35 days. On day 2 of admission, the patient underwent a frontal muscle jitter study that confirmed the MG, and electroneurography (ENG) and electromyography (EMG) that showed overlapping ICUAW with electrophysiological signs characteristic of CIP. The cerebrospinal fluid (CSF) showed normal pressure, cell count, and protein levels (<45 mg/dl) without albumin-cytologic disassociation. The CSF/serum glucose ratio was normal. The CSF culture for possible organisms, laboratory tests for autoimmune disorders, the panel of antiganglioside antibodies, and the paraneoplastic syndrome were negative. Strength and functional outcomes were tested with the MRC scale, the DRS, Barthel scale, and the Functional Independence Measure (FIM) at admission, discharge, and follow-up. Muscular strength improved progressively, and the MRC scale sum-score was 50 at discharge. Anticholinesterase therapy with pyridostigmine at a dosage of 30 mg 3 times daily, which the patient was taking before COVID-19, was resumed. His motor abilities recovered, and functional evaluations showed full recovery at follow-up. Conclusion In the described subject, the coexistence of both neuromuscular disorders did not affect the clinical course and recovery, but the question remains about generalization to all patients with MG. The rehabilitation interventions might have facilitated the outcome.